فاعلية الواقع المعزز في تنمية التحصيل الدراسي والتفكير الناقد لدى طالبات المرحلة الثانوية في مدينة الدمام واتجاهاتهن نحوه - الغامدي، إيمان امبارك عبدالله; قطب، إيمان محمد مبروك (المركز القومي للبحوث غزة, 2020)
هدف البحث إلى الكشف عن فاعلية الواقع المعزز في تنمية التحصيل الدراسي والتفكير الناقد لدى طالبات المرحلة الثانوية في محافظة الدمام في المملكة العربية السعودية واتجاهاتهن نحوه في مادة المكتبة والبحث، واستخدمت الباحثة المنهجين الوصفي وشبه التجريبي، وتكونت عينة البحث من (44) طالبة من طالبات الصف الأول الثانوي، تم تقسيمهن إلى مجموعتين، المجموعة التجريبية وعددهن (22) طالبة يستخدمن الواقع المعزز، والمجموعة الضابطة وعددهن (22) طالبة يستخدمن التعليم التقليدي، وقد استخدم البحث ثلاث أدوات تمثلت في اختبار تحصيلي ومقياس التفكير الناقد ومقياس الاتجاهات، وتوصل البحث إلى وجود فروق دالة إحصائيا عند مستوى الدلالة (0.05 ≥ α) بين متوسطات درجات طالبات المجموعة التجريبية التي تستخدم (الواقع المعزز) وطالبات المجموعة الضابطة التي تستخدم (التعليم التقليدي) في التطبيق البعدي للاختبار التحصيلي ومقياس التفكير الناقد لصالح المجموعة التجريبية، وكذلك وجود فروق دالة إحصائيا عند مستوى الدلالة (0.05 ≥ α) بين متوسطات درجات طالبات المجموعة التجريبية التي تستخدم (الواقع المعزز) في التطبيق القبلي والبعدي لمقياس الاتجاهات لصالح التطبيق البعدي، وأوصى البحث بضرورة استخدام تقنية الواقع المعزز في تدريس مادة المكتبة والبحث بشكل خاص ومهارات التفكير العليا المتضمنة في المواد الدراسية المختلفة بشكل عام.
The research aims to reveal the effectiveness of augmented reality in developing academic achievement and critical thinking for high school female students in Dammam Governorate in the Kingdom of Saudi Arabia and their attitudes towards it in the library and research course, The researcher used the descriptive and semi-experimental approaches, the research sample consisted of (44) female students from the first secondary class students, they were divided into two groups, the experimental group and their number (22) students use augmented reality, and the control group and their number (22) students use traditional education, the research used three tools represented in the achievement test, the scale of critical thinking, and the scale of trends, the research found that there are statistically significant differences at the level of significance (0.05 ≥ α) between the mean scores of students of the experimental group that use (augmented reality) and students of the control group that use (traditional education) in the post-application of the achievement test and the scale of critical thinking in favor of the experimental group, also, there are statistically significant differences at the significance level (0.05 ≥ α) between the mean scores of the students of the experimental group that use (augmented reality) in the pre and post application of the scale of trends in favor of the post application, the research recommended the necessity of using augmented reality technology in teaching library material and research in particular and the higher-order thinking skills included in the various subjects in general.
Keywords: التحصيل الدراسي -- التفكير الناقد -- طلبة المرحلة الثانوية -- الاتجاهات السلوكية